FEASIBILITY DECISION SUPPORT SYSTEM FOR RECIPIENTS OF BPNT (NON CASH FOOD ASSISTANCE) USING SAW METHOD AT BANE PEMATANGSIANTAR KELURAHAN WEB-BASED - Eduard Sihombing; Viktor Siregar; Novendra Damanik (INFOKUM, 2021)
Non-Cash Food Assistance (BPNT) is a program organized by the government in tackling poverty and food needs. The BPNT program aims to reduce expenses and provide more balanced nutrition to Beneficiary Families (KPM). However, in the implementation of the BPNT program, there are still technical problems, including the determination of the wrong target for BPNT recipients. To make it easier for relevant officials to determine prospective BPNT recipients, the authors create a decision support system using the Simple Additive Weighting method where this system produces a ranking as a recommendation for residents who are entitled to receive BPNT through the calculation of the weighting criteria of each alternative. It is hoped that this application can provide recommendations for prospective BPNT recipients that are more targeted.